2005
DOI: 10.1016/j.ydbio.2004.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Gli3 functions as both an activator and a repressor in Hedgehog signaling

Abstract: Hedgehog (Hh) signaling regulates cell differentiation and patterning in a wide variety of embryonic tissues. In vertebrates, at least three Gli transcription factors (Gli1, Gli2, and Gli3) are involved in Hh signal transduction. Comparative studies have revealed divergent requirements for Gli1 and Gli2 in zebrafish and mouse. Here, we address the question of whether Gli3 function has also diverged in zebrafish and analyze the regulatory interactions between Hh signaling and Gli activity. We find that zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 66 publications
7
108
0
Order By: Relevance
“…If Gli repressor activity is not present in MZsmo mutant ventral spinal cord until mid-somitogenesis stages, then this might be too late to repress the initial expression of progenitor domain genes and the formation of V2, V1 and V0v cells. Consistent with this, neither gli3 nor gli2a [both of which encode Gli proteins with repressor activity in zebrafish (Huang and Schier, 2009;Karlstrom et al, 1999;Karlstrom et al, 2003;Mich and Chen, 2011;Tyurina et al, 2005)] is clearly visible in the spinal cord until after 6 somites (12 hpf) in WT embryos or embryos with abrogated Hh signalling, although this does not rule out the possibility that there might be low levels of expression that remain undetected by in situ hybridisation (supplementary material Fig. S2).…”
Section: Medial Floorplate Still Forms In the Absence Of Hh Signallingmentioning
confidence: 74%
See 1 more Smart Citation
“…If Gli repressor activity is not present in MZsmo mutant ventral spinal cord until mid-somitogenesis stages, then this might be too late to repress the initial expression of progenitor domain genes and the formation of V2, V1 and V0v cells. Consistent with this, neither gli3 nor gli2a [both of which encode Gli proteins with repressor activity in zebrafish (Huang and Schier, 2009;Karlstrom et al, 1999;Karlstrom et al, 2003;Mich and Chen, 2011;Tyurina et al, 2005)] is clearly visible in the spinal cord until after 6 somites (12 hpf) in WT embryos or embryos with abrogated Hh signalling, although this does not rule out the possibility that there might be low levels of expression that remain undetected by in situ hybridisation (supplementary material Fig. S2).…”
Section: Medial Floorplate Still Forms In the Absence Of Hh Signallingmentioning
confidence: 74%
“…gli1 MO, 5Ј-CCGACACACCCGCTACACCCACAGT-3Ј (Huang and Schier, 2009;Karlstrom et al, 2003); gli2a MO, 5Ј-GGATGATGTAAAGTTCGTCAGTTGC-3Ј (Karlstrom et al, 2003); gli3 MO, 5Ј-ACAACTGGGCATTCCTCAGAGCATC-3Ј (Tyurina et al, 2005); p53 MO, 5Ј-GCGCCATTGCTTTGCAAGAATTG-3Ј (Robu et al, 2007). Previous studies have demonstrated that the Gli MOs specifically and efficiently knockdown Gli1, Gli2a and Gli3 (Huang and Schier, 2009;Karlstrom et al, 2003;Tyurina et al, 2005). The p53 (now called tp53) MO reduces non-specific off-target effects that are often associated with MOs (Huang and Schier, 2009;Robu et al, 2007).…”
Section: Mrna and Morpholino (Mo) Injectionsmentioning
confidence: 99%
“…In frogs, fish, mice and humans, Gli1 is a strong transcriptional activator; Gli2 has both activator and repressor functions; and Gli3 is mostly a repressor, although it can also have positive effects [4][5][6][7][8][9][10]. The fly Gli protein, Cubitus interruptus (Ci), is also both an activator and a repressor [11,12].…”
Section: Gli Proteins: Context-dependent Transcriptional Regulators Amentioning
confidence: 99%
“…In mice, it is mostly a weak activator of floor plate differentiation in the early CNS (Matise et al, 1998;Ding et al, 1998). Here, its function can be replaced by that of Gli1 (Bai and Joyner, 2001) but in zebrafish it harbors mostly negative function (Karlstrom et al, 1999;Karlstrom et al, 2003), although there is also evidence for limited positive effects (Tyurina et al, 2005). At late CNS stages, mouse Gli2 is required for normal brain growth and stem cell maintenance (Palma and Ruiz i Altaba, 2004).…”
Section: Introductionmentioning
confidence: 99%